Religious Character Formation in the Age of TikTok: Navigating Digital Disruption in Indonesian Islamic Elementary Schools - Masruroh Masruroh; Agus Wahdian; Ali Armadi (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The rapid pace of digitalization among elementary school children, particularly through social media such as TikTok, has raised concerns about the erosion of religious values instilled in madrasah environments. The emergence of the TikTok syndrome—characterized by dependence on short digital content—has the potential to shift children's focus away from religious practices and spiritual character development. Methodology: The study employs a descriptive quantitative approach using a survey method. The research subjects were 60 fifth-grade students at an elementary madrasah located in Sumenep Regency, selected through random sampling. The instrument used was a closed-ended questionnaire consisting of 25 statements, with two main variables: religious character and TikTok syndrome symptoms. Main Findings: The results of the study indicate that students generally have good religious character, as evidenced by their practice of praying five times a day, honesty, and respect for teachers and parents. However, the level of TikTok consumption is quite high, with some students showing signs of disruption, such as forgetting to study and delaying prayers. Novelty/Originality of this study: This study is among the first to empirically examine the intersection between TikTok usage and religious character formation in early-grade Islamic education. It introduces the concept of